Averting the Old-Age Crisis : Technical Annex - Palacios, J. Robert (The World Bank, 1999)
February 1996 - Supporting documentation for the World Bank publication Averting the Old Age Crisis: Policies to Protect the Old and Promote Growth (1994). Averting the Old Age Crisis: Policies to Protect the Old and Promote Growth, the publication for which this technical annex provides supporting documentation, is the third in a series of major World Bank Policy Research Reports. Unlike its predecessors, The East Asian Miracle and Adjustment in Africa, it does not concentrate on a specific region but focuses rather on the general topic of income security for old age. More than two years of research were required to gather data, review the theoretical literature, examine empirical evidence, and write the book that represents the Bank's most important study of the issue to date. This annex explains in detail the data sources, concepts, and definitions used in the book and provides additional information. It describes the demographic data used in the report and discusses data about public and privately managed pension schemes around the world (giving specific sources for individual countries). An attempt has been made to cross-reference the data available on ]STARS] diskettes, which can be downloaded and analyzed in most database or statistical software packages. This paper - a product of the Poverty and Human Resources Division, Policy Research Department - provides supporting documentation for the World Bank publication Averting the Old-Age Crisis: Policies to Protect the Old and Promote Growth (1994), available from the World Bank bookstore